INTEGRASI KEBIJAKAN INDUSTRI 4.0 DALAM PEMBANGUNAN EKONOMI BERBASIS TEKNOLOGI - Arya Tanta; Khaolatif Rabbani; Mubedi; Naerul Edwin Kiky Aprianto; Nuril Hadi Sofyan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
By combining advanced technologies such as artificial intelligence, the Internet of Things (IoT), big data, and automation, the industrial revolution 4.0 has changed the way theworld economy develops. This article talks about how Industry 4.0 policy can be incorporated into economic development technology-based, with a focus on efforts to create an ecosystem that supporting digital transformation. This method involves cooperation between government, industry, and educational institutions to support adoption new technology, strengthening digital infrastructure, and increasing competence human Resources. This study found strategic opportunities and problems key to implementing these policies in various industries. Study shows that productivity, global competitiveness, and growth An inclusive and sustainable economy can be enhanced through integration the right policy.